Unraveling waterlogging tolerance-related traits with QTL analysis in reciprocal intervarietal introgression lines using genotyping by sequencing in rapeseed (Brassica napus L.) - Xiao-yu DING; Jin-song XU; He HUANG; Xing QIAO; Ming-zhen SHEN; Yong CHENG; Xue-kun ZHANG (Journal of Integrative Agriculture, 2020)
Soil waterlogging is a major environmental stress that suppresses the growth and productivity of rapeseed (Brassica napus L.). Natural genetic variations in waterlogging tolerance (WT) were observed but no QTL mapping has been done for WT related traits in rapeseed. In this study, QTL associated with three WT related traits including relative root length (RRL), relative hypocotyl length (RHL) and relative fresh weight (RFW) were dissected using a set of reciprocal introgression lines (ILs) derived from the cross GH01×ZS9, which showed significant difference in WT. Genotyping-by-sequencing (GBS) of the populations were performed, totally 1 468 and 1 450 binned SNPs were identified for GIL (GH01 as the recurrent parent) and ZIL (ZS9 as the recurrent parent) population, respectively. A total of 66 distinct QTLs for WT at the seedling establishment stage including 31 for RRL, 17 for RHL and 18 for RFW were detected. Among the 66 QTLs, 20 (29.4%) QTLs were detected in both genetic backgrounds and then they were integrated into six QTL clusters, which can be targeted in rapeseed breeding for improvement of WT through marker-assisted selection (MAS). Based on the physical positions of SNPs and the functional annotation of the Arabidopsis thaliana genome, 56 genes within the six QTL cluster regions were selected as preliminary candidate genes, then the resequencing and transcriptome information about parents were applied to narrow the extent of candidate genes. Twelve genes were determined as candidates for the six QTL clusters, some of them involved in RNA/protein degradation, most of them involved in oxidation-reduction process. These findings provided genetic resources, candidate genes to address the urgent demand of improving WT in rapeseed breeding.